Alginate/acemannan-based beads loaded with a biocompatible ionic liquid as a bioactive delivery system - Gomes, Joana M. (2023)
Combining biomacromolecules with green chemistry principles and clean technologies has proven to be an effective approach for drug delivery, providing a prolonged and sustained release of the encapsulated material. The current study investigates the potential of cholinium caffeate (Ch[Caffeate]), a phenolic-based biocompatible ionic liquid (Bio-IL) entrapped in alginate/acemannan beads, as a drug delivery system able to reduce local joint inflammation on osteoarthritis (OA) treatment. The synthesized Bio-IL has antioxidant and anti-inflammatory actions that, combined with biopolymers as 3D architectures, promote the entrapment and sustainable release of the bioactive molecules over time. The physicochemical and morphological characterization of the beads (ALC, ALAC0,5, ALAC1, and ALAC3, containing 0, 0.5, 1, and 3 %(w/v) of Ch[Caffeate], respectively) revealed a porous and interconnected structure, with medium pore sizes ranging from 209.16 to 221.30 Î¼m, with a high swelling ability (up 2400 %). Ch[Caffeate] significantly improved the antioxidant activities of the constructs by 95 % and 97 % for ALAC1 and ALAC3, respectively, when compared to ALA (56 %). Besides, the structures provided the environment for ATDC5 cell proliferation, and cartilage-like ECM formation, supported by the increased GAGs in ALAC1 and ALAC3 formulations after 21 days. Further, the ability to block the secretion of pro-inflammatory cytokines (TNF-Î± and IL-6), from differentiated THP-1 was evidenced by ChAL-Ch[Caffeate] beads. These outcomes suggest that the established strategy based on using natural and bioactive macromolecules to develop 3D constructs has great potential to be used as therapeutic tools for patients with OA.